Sulfur-rich polymer and preparation method thereof, composition for waterproof coating, waterproof coating and preparation method and application of waterproof coating

By preparing sulfur-rich polymers and applying them to waterproof coatings, the problems of insufficient bonding properties and mechanical strength of existing waterproof coatings are solved, and waterproof coatings with high bonding strength, mechanical strength and self-repairing ability are achieved.

CN119591785AActive Publication Date: 2025-03-11GUANGDONG YILAIDE BUILDING MATERIAL CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411777827.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-11
Estimated Expiration
2044-12-05

AI Technical Summary

Technical Problem

The existing functional waterproof coatings have problems such as insufficient initial bonding strength, low mechanical strength and poor aging resistance, which leads to the coating film being easily damaged by external forces and insufficient self-repair ability.

Method used

A method for preparing a sulfur-rich polymer is adopted, including reacting sulfur, itaconic acid and dimethylaminopropylmethacrylamide in the presence of a protective gas and a catalyst to obtain an intermediate product and then dry to obtain a sulfur-rich polymer. As the main component of the waterproof coating, the sulfur-rich polymer combines composite polymer emulsion, fillers and additives to form a waterproof coating with high bonding properties and mechanical strength.

Benefits of technology

It significantly improves the initial bonding strength and mechanical strength of the paint, improves the problem of waterproofing and easy bubbling on the roof, and has the ability to repair itself in a long-term exposed environment, extending the bonding performance between the coating and the base layer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005171953150000101
    Figure BDA0005171953150000101
  • Figure BDA0005171953150000121
    Figure BDA0005171953150000121
  • Figure BDA0005171953150000131
    Figure BDA0005171953150000131
Patent Text Reader

Abstract

The invention relates to the field of waterproof coatings, and discloses a sulfur-rich polymer and a preparation method thereof, a composition for a waterproof coating, the waterproof coating and a preparation method and application of the waterproof coating. The method for preparing the sulfur-rich polymer comprises the following steps: S1, reacting sulfur, itaconic acid and dimethylaminopropyl methacrylamide in the presence of protective gas and a catalyst to obtain an intermediate product; s2, drying the intermediate product to obtain a sulfur-rich polymer; the dosage mass ratio of the sulfur to the itaconic acid to the dimethylaminopropyl methacrylamide is 1: (0.8-1.2): (2.0-3.2). The waterproof coating prepared from the sulfur-rich polymer provided by the invention can solve the problems of poor adhesive property, mechanical strength and aging resistance of the existing functional waterproof coating, and effectively improves the phenomenon that the roof waterproof coating is easy to blister and swell.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of waterproof coatings, and in particular to a sulfur-rich polymer and a preparation method thereof, a composition for waterproof coatings, a waterproof coating and a preparation method and application thereof. Background Art

[0002] At present, the market demand for the use of multifunctional coatings is gradually increasing, which has led to the rapid development of various multifunctional coatings such as rust-proof waterproof coatings, aging-resistant waterproof coatings, sound-insulating waterproof coatings, and flame-retardant waterproof coatings.

[0003] However, as the functionality of existing waterproof materials increases, their basic properties such as adhesion and durability will decrease. The coating film is easily damaged by the impact and friction of the external environment during use. After years of damage, the coating layer will form larger and larger cracks or openings, eventually leading to waterproof failure. At present, we are in urgent need of a functional coating that can not only ensure good adhesion and make the material adhere tightly, but also have excellent mechanical strength to resist external forces. At the same time, it can self-repair in an environment exposed for a long time to achieve good adhesion with the base layer to meet complex waterproofing needs.

[0004] For example, CN111574126A discloses a self-repairing polymer cement waterproof coating and its preparation method. The waterproof coating is composed of liquid and powder, and the liquid contains self-repairing core-shell capsules. The shell of the capsule is resin, and the core is composed of sodium alginate, polyoxyethylene octadecylamine, super-hydrophobic silica aerogel powder, and water. When fine cracks appear in the coating, the shell of the capsule breaks, and the sodium alginate comes into contact with the calcium hydroxide after cement hydration. 2+ Under the action of , cross-linking occurs, forming a three-dimensional network to seal the cracks. Although this solution has a self-healing effect, its principle is to use microcapsules and the substances they contain to produce effects. The self-healing function of the microcapsules in this solution is one-time, and if the microcapsule ingredients are small, the self-healing performance is not strong, and if the ingredients are large, it will affect the material's own strength and bonding strength. Summary of the invention

[0005] The purpose of the present invention is to solve the problems of insufficient initial bonding strength of the functional waterproof coating in the prior art, which leads to bubbling and falling off, as well as low mechanical strength and poor aging resistance.

[0006] In order to achieve the above object, the first aspect of the present invention provides a method for preparing a sulfur-rich polymer, the method comprising:

[0007] S1. In the presence of protective gas and catalyst, sulfur, itaconic acid and dimethylaminopropyl methacrylamide are reacted to obtain an intermediate product; the reaction conditions include: temperature of 160-180° C., time of 2-5 hours; the catalyst is zinc diethyldithiocarbamate;

[0008] S2, drying the intermediate product to obtain the sulfur-rich polymer;

[0009] The mass ratio of the sulfur, the itaconic acid and the dimethylaminopropyl methacrylamide is 1:0.8-1.2:2.0-3.2.

[0010] The second aspect of the present invention provides a sulfur-rich polymer prepared by the method described in the first aspect.

[0011] The third aspect of the present invention provides a waterproof coating composition, which contains a main agent and an auxiliary agent:

[0012] The main agent includes a composite polymer emulsion, a filler and a component A; the auxiliary agent includes at least one of a thickener, a dispersant and a defoamer;

[0013] Based on the total weight of the composition, the composition contains 40-60 wt% of a composite polymer latex, 20-35 wt% of a filler, 10-30 wt% of a component A and 0.4-11.5 wt% of an auxiliary agent;

[0014] The component A is an ethanol solution of a sulfur-rich polymer with a concentration of 25-40wt%; the sulfur-rich polymer is the sulfur-rich polymer described in the second aspect;

[0015] The composite polymer emulsion is a combination of a silicone-acrylic emulsion and a styrene-acrylic emulsion in a mass ratio of 1:2-3.5; the glass transition temperature of the silicone-acrylic emulsion is 19-23°C.

[0016] The fourth aspect of the present invention provides a method for preparing a waterproof coating, which is carried out using the composition described in the third aspect, comprising:

[0017] (1) mixing a first mixture containing a dispersant, a defoaming agent and a portion of the composite polymer emulsion to obtain a material I; the first mixture optionally contains water and a preservative;

[0018] (2) performing a second mixing of the filler and the material I to obtain a material II;

[0019] (3) Component A, the thickener, the remaining composite polymer emulsion and material II are mixed for the third time to obtain the waterproof coating.

[0020] The fifth aspect of the present invention provides a waterproof coating prepared by the method described in the fourth aspect.

[0021] The sixth aspect of the present invention provides the use of the waterproof coating described in the fifth aspect in waterproofing the exposed roof of a building.

[0022] The waterproof coating prepared by the sulfur-rich polymer provided by the present invention effectively solves the problems of poor bonding performance and mechanical strength of existing functional waterproof coatings, and effectively improves the phenomenon of easy bubbling and bulging of roof waterproofing;

[0023] At the same time, the waterproof coating prepared by the sulfur-rich polymer provided by the present invention can self-repair under long-term exposure to the sun, and can also effectively avoid the problem of reduced ornamental and functional properties caused by the growth of microorganisms on the coating surface due to long-term rainy weather and high dust in the air. DETAILED DESCRIPTION

[0024] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0025] As mentioned above, the first aspect of the present invention provides a method for preparing a sulfur-rich polymer, the method comprising:

[0026] S1. In the presence of protective gas and catalyst, sulfur, itaconic acid and dimethylaminopropyl methacrylamide are reacted to obtain an intermediate product; the reaction conditions include: temperature of 160-180° C., time of 2-5 hours; the catalyst is zinc diethyldithiocarbamate;

[0027] S2, drying the intermediate product to obtain the sulfur-rich polymer;

[0028] The mass ratio of the sulfur, the itaconic acid and the dimethylaminopropyl methacrylamide is 1:0.8-1.2:2.0-3.0.

[0029] Preferably, in step S2, the drying conditions include: temperature of 120-130°C and time of 20-40 min.

[0030] Preferably, the protective gas is selected from at least one of nitrogen and argon.

[0031] Preferably, the amount of the catalyst is 0.8-1.2 wt % based on the total mass of the sulfur, the itaconic acid and the dimethylaminopropyl methacrylamide.

[0032] As mentioned above, the second aspect of the present invention provides a sulfur-rich polymer prepared by the method described in the first aspect.

[0033] Preferably, the sulfur-rich polymer has a softening point of 43-55° C., a needle penetration of 50-70 / 0.1 mm, and an average number average molecular weight of 400-1000 g / mol.

[0034] As mentioned above, the third aspect of the present invention provides a waterproof coating composition, which contains a main agent and an auxiliary agent:

[0035] The main agent includes a composite polymer emulsion, a filler and a component A; the auxiliary agent includes at least one of a thickener, a dispersant and a defoamer;

[0036] Based on the total weight of the composition, the composition contains 40-60 wt% of a composite polymer latex, 20-35 wt% of a filler, 10-30 wt% of a component A and 0.4-11.5 wt% of an auxiliary agent;

[0037] The component A is an organic solution of a sulfur-rich polymer with a concentration of 25-40 wt%; the sulfur-rich polymer is the sulfur-rich polymer described in the second aspect above;

[0038] The composite polymer emulsion is a combination of a silicone-acrylic emulsion and a styrene-acrylic emulsion in a mass ratio of 1:2-3.5; the glass transition temperature of the silicone-acrylic emulsion is 19-23°C.

[0039] Preferably, the organic solution in the organic solution of 25-40 wt % of sulfur-rich polymer is selected from at least one of methanol, ethanol and N,N-dimethylformamide; more preferably, it is ethanol.

[0040] Preferably, the auxiliary agent also includes a preservative; based on the total mass of the composition, the composition contains 40-60wt% of a composite polymer emulsion, 10-30wt% of component A, 0.1-0.4wt% of a thickener, 0.1-0.5wt% of a dispersant, 0.1-0.3wt% of a defoamer, 20-35wt% of a filler and 0.1-0.3wt% of a preservative.

[0041] More preferably, the auxiliary agent also includes water; based on the total mass of the composition, the composition contains 40-45wt% of composite polymer emulsion, 15-20wt% of component A, 0.1-0.4wt% of thickener, 0.1-0.5wt% of dispersant, 0.1-0.3wt% of defoamer, 20-28wt% of filler, 8-10wt% of water and 0.1-0.3wt% of preservative. The inventors found that under this preferred embodiment, the waterproof coating obtained has better bonding performance and mechanical strength, while taking into account better self-repairing effect and antibacterial effect.

[0042] Preferably, the glass transition temperature of the styrene acrylic emulsion is -19 to -15° C. The inventors found that under this preferred embodiment, the obtained waterproof coating has better bonding performance and mechanical strength.

[0043] Preferably, in order to increase the bonding strength between the coating and the base layer and the self-repairing ability of the coating, the component A is an ethanol solution of a sulfur-rich polymer with a concentration of 30-35 wt%.

[0044] Preferably, in order to improve the workability and storage stability of the coating, the thickener is selected from at least one of an alkali swelling thickener and an associative polyurethane thickener.

[0045] In order to further improve the dispersing effect of the system, in the present invention, the dispersant is preferably at least one of polyacrylate, polyphosphate and polycarboxylate.

[0046] Preferably, the preservative is selected from at least one of 1,2-benzisothiazolinone, methylisothiazolinone, methylchloroisothiazolinone and 1,2-benzisothiazolin-3-one; the inventors found that under this preferred condition, the waterproof coating obtained by the present invention has a better inhibitory effect on microorganisms.

[0047] Preferably, the filler is selected from at least one of heavy calcium, barium sulfate and titanium dioxide.

[0048] In order to further improve the density of the coating, the filler is more preferably a combination of heavy calcium and titanium dioxide.

[0049] As mentioned above, the fourth aspect of the present invention provides a method for preparing a waterproof coating, which is carried out using the composition described in the third aspect, comprising:

[0050] (1) mixing a first mixture containing a dispersant, a defoaming agent and a portion of the composite polymer emulsion to obtain a material I; the first mixture optionally contains water and a preservative;

[0051] (2) performing a second mixing of the filler and the material I to obtain a material II;

[0052] (3) Component A, the thickener, the remaining composite polymer emulsion and material II are mixed for the third time to obtain the waterproof coating.

[0053] It should be noted that in step (1), there is no particular requirement for the specific amount of the partial composite polymer emulsion, as long as it is mixed evenly; in order to obtain a more uniform and delicate coating, preferably, the partial composite polymer emulsion in step (1) can be 30-50wt% of the total amount.

[0054] Preferably, the first mixing, the second mixing and the third mixing are each independently performed under stirring conditions;

[0055] In step (1), the first mixing conditions include: stirring speed of 450-900 rpm, time of 3-5 min, and temperature of 5-35°C.

[0056] Preferably, in step (2), the second mixing conditions include: stirring speed of 1000-2000 rpm, time of 30-60 min, and temperature of 5-35°C.

[0057] Preferably, in step (3), the conditions for the third mixing include: a stirring speed of 1000-1500 rpm, a time of 10-30 min, and a temperature of 5-35°C.

[0058] More preferably, in step (1), the method further comprises premixing water and part of the composite polymer emulsion, wherein the premixing conditions comprise: a temperature of 5-35° C., a stirring speed of 550-650 rpm, and a time of 1-2 min.

[0059] As mentioned above, the fifth aspect of the present invention provides a waterproof coating prepared by the method described in the fourth aspect.

[0060] As mentioned above, the sixth aspect of the present invention provides the use of the waterproof coating described in the fifth aspect in waterproofing the exposed roof of a building.

[0061] The present invention will be described in detail below through examples.

[0062] In the following examples, unless otherwise specified, all reagents and raw materials involved are commercially available, and all reagents are analytically pure products.

[0063] In the following examples, unless otherwise specified, each wt% represents 0.1 kg.

[0064] raw material:

[0065] Styrene acrylic emulsion I: model: 5619, glass transition temperature: -19°C, purchased from Shanghai Baolijia Chemical Co., Ltd.;

[0066] Styrene acrylic emulsion II: model: 7117, glass transition temperature is -9 °C, purchased from Jinyoulai Industry and Trade Co., Ltd.;

[0067] Silicone acrylic emulsion I: model: 8392, glass transition temperature: 23°C, purchased from Guangdong Yinyang Environmental Protection New Materials Co., Ltd.;

[0068] Silicone acrylic emulsion II: model: KD96, glass transition temperature: 36°C, purchased from Shanghai Baolijia Chemical Co., Ltd.;

[0069] Composite polymer emulsion I: a combination of silicone-acrylic emulsion I and styrene-acrylic emulsion I in a mass ratio of 1:2.5;

[0070] Composite polymer emulsion II: a combination of silicone-acrylic emulsion I and styrene-acrylic emulsion II in a mass ratio of 1:2.5;

[0071] Composite polymer emulsion III: a combination of silicone-acrylic emulsion II and styrene-acrylic emulsion II in a mass ratio of 1:2.5;

[0072] Composite polymer emulsion IV: a combination of silicone-acrylic emulsion I and styrene-acrylic emulsion I in a content mass ratio of 1:0.7;

[0073] Thickener: polyurethane, brand U505, purchased from Wanhua Chemical Group Co., Ltd.

[0074] Dispersant: polycarboxylate ammonium salt, brand 5027, purchased from Guangzhou Meicheng New Material Technology Co., Ltd.;

[0075] Defoaming agent: modified silicone, brand DF1668, purchased from Foshan Keerle Building Materials Co., Ltd.

[0076] Filler: a combination of titanium dioxide and heavy calcium in a mass ratio of 1:5.75;

[0077] Preservatives: 5-chloro-2-methyl-4-isothiazoline-3-one and 2-methyl-4-isothiazoline-3-one, brand name Kasson, purchased from Jinan Sunny Chemical Technology Co., Ltd.

[0078] Preparation Example 1

[0079] This preparation example is used to illustrate that the sulfur-rich polymer described in the present invention is prepared according to the following method.

[0080] The method for preparing the sulfur-rich polymer comprises the following steps:

[0081] S1. In the presence of nitrogen and zinc diethyldithiocarbamate, sulfur, itaconic acid and dimethylaminopropyl methacrylamide are reacted to obtain an intermediate product; the reaction conditions are: temperature 165° C., time 3.5 h;

[0082] S2, drying the intermediate product to obtain the sulfur-rich polymer Z1;

[0083] The drying conditions are: temperature of 120° C., time of 30 min; based on the total mass of the sulfur, the itaconic acid, and the dimethylaminopropyl methacrylamide, the amount of the catalyst is 1 wt %;

[0084] The mass ratio of the sulfur, the itaconic acid and the dimethylaminopropyl methacrylamide is 1:1:3.

[0085] The sulfur-rich polymer has a softening point of 52° C., a needle penetration of 66 / 0.1 mm, and an average number average molecular weight of 700 g / mol.

[0086] Preparation Example 2

[0087] This preparation example adopts a process similar to that of Preparation Example 1, except that in this preparation example, the amount of sulfur used is controlled to be the same as that of Preparation Example 1, but the mass ratio of sulfur, itaconic acid, and dimethylaminopropyl methacrylamide is 1:1:1. The remaining preparation steps and process conditions are the same as those of Preparation Example 1. Polymer Z2 is prepared.

[0088] Preparation Example 3

[0089] This preparation example adopts a process similar to that of Preparation Example 1, except that in this preparation example, the amount of sulfur used is controlled to be the same as that of Preparation Example 1, but the mass ratio of sulfur, itaconic acid, and dimethylaminopropyl methacrylamide is 3:1:3. The remaining preparation steps and process conditions are the same as those of Preparation Example 1. Polymer Z3 is prepared.

[0090] Example 1

[0091] This example is used to illustrate that the waterproof coating of the present invention is prepared according to the formulation in Table 1 and the method described below.

[0092] The method for preparing the waterproof coating comprises the following steps:

[0093] (1) mixing a first mixture containing a dispersant, water, a preservative, a defoamer and 40 wt% of the total amount of the composite polymer emulsion to obtain a material I; the first mixing conditions are: a stirring speed of 800 rpm, a time of 3 min, and a temperature of 25° C.;

[0094] (2) performing a second mixing of the filler and the material I to obtain a material II; the conditions of the second mixing are: a stirring speed of 1500 rpm, a time of 40 min, and a temperature of 25° C.;

[0095] (3) Component A, thickener, remaining composite polymer emulsion and material II are mixed for the third time to obtain the waterproof coating. The conditions of the third mixing are: stirring speed of 1500 rpm, time of 20 minutes, and temperature of 25°C.

[0096] Unless otherwise specified, the remaining examples were carried out using a process similar to that of Example 1, except that the formulations used in each example were different, as shown in Table 1 (Note: the parameters not listed in Table 1 are the same as the corresponding parameters in Example 1).

[0097] Table 1

[0098]

[0099]

[0100] Example 4

[0101] This example is carried out using a process similar to that of Example 1, except that, in this example, an equal mass of composite polymer emulsion II is used to replace the composite polymer emulsion I in Example 1.

[0102] The rest are the same as in Example 1.

[0103] The waterproof coating S4 is prepared.

[0104] Example 5

[0105] This embodiment is carried out using a process similar to that of Embodiment 1, except that, in this embodiment, an ethanol solution of Z1 with a concentration of 40 wt % is used to replace the ethanol solution of Z1 with a concentration of 30 wt % in Embodiment 1.

[0106] The rest are the same as in Example 1.

[0107] The waterproof coating S5 was prepared.

[0108] Example 6

[0109] This example is carried out using a process similar to that of Example 1, except that, in this example, an equal mass of composite polymer emulsion III is used to replace the composite polymer emulsion I in Example 1.

[0110] The rest are the same as in Example 1.

[0111] The waterproof coating S6 was prepared.

[0112] Example 7

[0113] This example is carried out using a process similar to that of Example 1, except that, in this example, an equal mass of composite polymer emulsion IV is used to replace the composite polymer emulsion I in Example 1.

[0114] The rest are the same as in Example 1.

[0115] The waterproof coating S7 was prepared.

[0116] Comparative Example 1

[0117] This comparative example is carried out using a process similar to that of Example 1, except that in this comparative example, an equal mass of a 30wt% ethanol solution of Z2 is used to replace the 30wt% ethanol solution of Z1 in Example 1.

[0118] The rest are the same.

[0119] The waterproof coating DS1 was prepared.

[0120] Comparative Example 2

[0121] This comparative example is carried out using a process similar to that of Example 1, except that in this comparative example, an equal mass of a 30wt% ethanol solution of Z3 is used to replace the 30wt% ethanol solution of Z1 in Example 1.

[0122] The rest are the same as in Example 1.

[0123] The waterproof coating DS2 was prepared.

[0124] Comparative Example 3

[0125] This comparative example was carried out using a process similar to that of Example 1, except that, in this comparative example, equal masses of Z1 and ethanol solution (the mass of Z1 and the amount of ethanol used were the same as in Example 1, but the two components were added independently during the preparation process) were used to replace the 30 wt% ethanol solution of Z1 in Example 1.

[0126] The rest are the same as in Example 1.

[0127] The waterproof coating DS3 was prepared.

[0128] Test Case

[0129] 1. Mechanical properties test: Tested according to GB / T 23445-2009;

[0130] 2. Bond strength test after artificial weathering treatment: The untreated bond strength specimens prepared according to GB / T 23445-2009 were treated according to the method of 5.4.3.3 in JC / T 864-2008 (five specimens). After the test, they were placed under standard test conditions for 4 hours, and then their bond strength was tested according to the steps of 7.6.3.1 in GB / T 23445-2009;

[0131] 3. Antibacterial effect test: The antibacterial performance test method of the antibacterial coating is tested according to HG / T 3950-2007, and the tested bacteria are Escherichia coli and Staphylococcus aureus;

[0132] 4. Self-repairing performance test: Use GB / T 23445-2009 test specimens for watertightness, use a 0.5mm thick utility knife to cut a 10mm long knife gap in the middle of the specimen, then place the specimen flat in a 60℃ oven for curing for 24h, and after cooling, test the watertightness at 0.05MPa for 30min. If all three specimens are watertight, it passes; if one or two are watertight, it partially passes; if all three are watertight, it fails.

[0133] The performance of the waterproof coating obtained in each example was tested using the above test method, and the test results are shown in Table 2.

[0134] Table 2

[0135]

[0136]

[0137] From the results in Table 2, it can be seen that the sulfur-rich polymer prepared by the present invention has significant effects after being applied to waterproof coatings. It significantly improves the initial bonding strength of the coating, and the bonding strength is still high after 720 hours of artificial weathering treatment. This feature effectively solves the problem of the waterproof layer failing due to bubbling and shedding in actual use. In addition, the product also has excellent self-repairing and antibacterial functions, which effectively guarantees the integrity of the coating film and the neatness of the appearance during use, greatly prolongs the effective use period of the product and improves its performance.

[0138] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A method for preparing a sulfur-rich polymer, characterized in that: The method includes: S1. In the presence of protective gas and catalyst, sulfur, itaconic acid and dimethylaminopropyl methacrylamide are reacted to obtain an intermediate product; the reaction conditions include: temperature of 160-180° C., time of 2-5 hours; the catalyst is zinc diethyldithiocarbamate; S2, drying the intermediate product to obtain the sulfur-rich polymer; The mass ratio of the sulfur, the itaconic acid and the dimethylaminopropyl methacrylamide is 1:0.8-1.2:2.0-3.

2.

2. The method according to claim 1, characterized in that In step S2, the drying conditions include: temperature of 120-130°C and time of 20-40 minutes; And / or, based on the total mass of the sulfur, the itaconic acid and the dimethylaminopropyl methacrylamide, the amount of the catalyst is 0.8-1.2 wt %.

3. The sulfur-rich polymer prepared by the method according to claim 1 or 2; Preferably, the sulfur-rich polymer has a softening point of 43-55° C., a needle penetration of 50-70 / 0.1 mm, and a number average molecular weight of 400-1000 g / mol.

4. A waterproof coating composition, characterized in that: The composition contains the main agent and auxiliary agents: The main agent includes a composite polymer emulsion, a filler and a component A; the auxiliary agent includes at least one of a thickener, a dispersant and a defoamer; Based on the total weight of the composition, the composition contains 40-60 wt% of a composite polymer latex, 20-35 wt% of a filler, 10-30 wt% of a component A and 0.4-11.5 wt% of an auxiliary agent; The component A is an organic solution of a sulfur-rich polymer with a concentration of 25-40 wt%; the sulfur-rich polymer is the sulfur-rich polymer according to claim 3; The composite polymer emulsion is a combination of a silicone-acrylic emulsion and a styrene-acrylic emulsion in a mass ratio of 1:2-3.5; the glass transition temperature of the silicone-acrylic emulsion is 19-23°C; Preferably, the organic solution in the organic solution of 25-40 wt % of sulfur-rich polymer is selected from at least one of methanol, ethanol and N,N-dimethylformamide; more preferably, it is ethanol.

5. The composition according to claim 4, characterized in that The auxiliary agent also includes a preservative; based on the total mass of the composition, the composition contains 40-60wt% of a composite polymer emulsion, 10-30wt% of a component A, 20-35wt% of a filler, 0.1-0.4wt% of a thickener, 0.1-0.5wt% of a dispersant, 0.1-0.3wt% of a defoamer and 0.1-0.3wt% of a preservative; Preferably, the auxiliary agent also includes water; based on the total mass of the composition, the composition contains 40-45wt% of composite polymer emulsion, 15-20wt% of component A, 0.1-0.4wt% of thickener, 0.1-0.5wt% of dispersant, 0.1-0.3wt% of defoamer, 20-28wt% of filler, 8-10wt% of water and 0.1-0.3wt% of preservative.

6. The composition according to claim 4 or 5, characterized in that The glass transition temperature of the styrene acrylic emulsion is -19 to -15°C; And / or, the component A is an ethanol solution of a sulfur-rich polymer with a concentration of 30-35 wt%.

7. A method for preparing a waterproof coating, characterized in that: The method is carried out using the composition described in any one of claims 4 to 6, comprising: (1) mixing a first mixture containing a dispersant, a defoaming agent and a portion of the composite polymer emulsion to obtain a material I; the first mixture optionally contains water and a preservative; (2) performing a second mixing of the filler and the material I to obtain a material II; (3) Component A, the thickener, the remaining composite polymer emulsion and material II are mixed for the third time to obtain the waterproof coating.

8. The method according to claim 7, characterized in that The first mixing, the second mixing and the third mixing are each independently performed under stirring conditions; In step (1), the first mixing conditions include: stirring speed of 450-900 rpm, time of 3-5 min, temperature of 5-35° C.; And / or, in step (2), the second mixing conditions include: stirring speed of 1000-2000 rpm, time of 30-60 min, temperature of 5-35°C; And / or, in step (3), the conditions of the third mixing include: stirring speed of 1000-1500 rpm, time of 10-30 min, and temperature of 5-35°C.

9. A waterproof coating prepared by the method according to claim 7 or 8.

10. Use of the waterproof coating according to claim 9 in waterproofing of exposed roofs of buildings.

Citation Information

Patent Citations

  • High-molecular-weight soluble elementary sulfur / terpene copolymer, and preparation method and application of same

    CN107501453A

  • Spraying quick-setting waterborne polyurethane modified asphalt waterproof coating and preparation method thereof

    CN113122136A

  • Waterproof coating composition, waterproof coating and preparation method and application thereof

    CN113845802A

  • Environmentally friendly flame-retardant heat-insulating paint and its manufacturing method

    JP7509486B1